Electrodialytic recovery of rare earth elements from coal ashes - Couto, Nazaré (2022)
Fundação para a Ciência e a Tecnologia, I.P., Portugal, UIDB/04085/2020 (Research unit CENSE “Center for Environmental and Sustainability Research”). Fundação para a Ciência e a Tecnologia is also acknowledged for N. Couto Contract established under Individual Call to Scientific Employment Stimulus (CEECIND/04210/2017).